Psychosocial Therapies for Chronic Headache - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Psychosocial interventions in the management of recurrent headache disorders are reviewed from Ohio University, Athens, OH, and University of Mississippi Medical Center, Jackson, MS.